2005
DOI: 10.1111/j.1572-0241.2005.41126.x
|View full text |Cite
|
Sign up to set email alerts
|

A Polymorphism in the TNF-alpha Promoter Gene is Associated with Pediatric Onset and Colonic Location of Crohn's Disease

Abstract: Pediatric onset of CD in our population was associated with a frequent polymorphism in the binding site for NF-kappaB in TNF-alpha promoter but not to defined NOD2/CARD15 disease-associated mutations. This polymorphism is associated with colitis and familial disease. NOD2/CARD15 mutations and the TNF-863C/A polymorphism have equivalent but opposite effects on disease location. These findings may help explain differences in CD phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
1

Year Published

2006
2006
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 39 publications
0
31
1
Order By: Relevance
“…Mutations of the TNF-␣ promoter gene were analyzed by pyrosequencing technology (35). Polymerase chain reaction was performed in a 50 L volume containing 10 mM tris-HCl, pH 8.3, 50 mM KCl, 1.5 mM MgCl 2 , 250 M dNTPs, 1 M of each primer, 200 ng of genomic DNA and 1.25U of AmpiTaq Gold DNA polymerase (Perkin Elmer Applied Biosystem) with an initial denaturation step of 10min at 95°C to activate the polymerase followed by 35 cycles of 94°C; 15 s, 60°C; 45 s, 72°C; 45 s and final elongation of 10 min at 72°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutations of the TNF-␣ promoter gene were analyzed by pyrosequencing technology (35). Polymerase chain reaction was performed in a 50 L volume containing 10 mM tris-HCl, pH 8.3, 50 mM KCl, 1.5 mM MgCl 2 , 250 M dNTPs, 1 M of each primer, 200 ng of genomic DNA and 1.25U of AmpiTaq Gold DNA polymerase (Perkin Elmer Applied Biosystem) with an initial denaturation step of 10min at 95°C to activate the polymerase followed by 35 cycles of 94°C; 15 s, 60°C; 45 s, 72°C; 45 s and final elongation of 10 min at 72°C.…”
Section: Methodsmentioning
confidence: 99%
“…Polymorphisms that have been reported to increase (308G/A) or decrease circulating TNF-␣ (238G/A, 857 C/T, 863 C/A) (27)(28)(29)(30)(31)(32)(33), as well as playing a possible role in disease phenotype and susceptibility (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). The 857C/T and 863C/A polymorphisms appear to be located at transcription factor binding sites (32,34,35).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Vatay et al [29] also showed an increased risk in their study on Hungarian subjects. However, several negative studies have been published, including Levine et al [48] who examined a pediatric Jewish population, and Sashio et al [28] in a study on Japanese patients. In particular, the latter authors found a difference in the carrier frequency for haplotype AG (-308 A, -238 Japanese 217 Vatay [29] Hungarian 188 Kim [30] Korean 291 Celik [33] Turkish 225 Yamamoto-Mexican 179 Furusho [34] Current study NZ 820…”
mentioning
confidence: 99%
“…Interestingly, this variant was also associated with CD when they left out the common NOD2 allele carriers, meaning that these genes act independently to confer CD susceptibility. Pediatric onset, colonic disease and familial aggregation of CD was associated with the c.-863C>A polymorphism, which is located within a binding site for NF B in the TNF promoter [124]. Moreover, it was demonstrated that exposure of 293T cells to bacterial components stimulates TNF gene transcription as a result of NOD2-induced NF B activation [125].…”
Section: Tnf (6p)mentioning
confidence: 99%